Real-World Data of Tigecycline-Associated Drug-Induced Liver Injury Among Patients in China: A 3-year Retrospective Study as Assessed by the Updated RUCAM - Shi, Xiaoping; Zuo, Chengchun; Yu, Lingling; Lao, Donghui; Li, Xiaoyu; Xu, Qing; Lv, Qianzhou (Frontiers in Pharmacology, 2021)
Background: Tigecycline, a glycylcycline antibiotic, is increasingly used clinically for the treatment of severe infections caused by multidrug-resistant bacteria, but it is also associated with hepatotoxicity. However, the incidence and risk factors of tigecycline-associated drug-induced liver injury (DILI) are unclear. We conducted this study to investigate the incidence, characteristics and risk factors of tigecycline-associated DILI in the real-world clinic setting. Patients and Methods: A retrospective analysis was conducted in inpatients who received tigecycline treatment from January 2018 to January 2020. Based on the biochemical criteria of DILI and the causality assessment by Roussel Uclaf Causality Assessment Method (RUCAM) using cases with a probable or highly probable causality grading, two clinical pharmacists and one clinician worked together to screen patients for tigecycline-associated DILI. Then patients with DILI were randomly matched by gender in a ratio of 1:2 to the remaining patients in the tigecycline cohort without biochemical abnormalities to identify risk factors. Results: A total of 973 patients from 1,250 initial participants were included. The incidence of tigecycline-associated DILI was 5.7% (55/973. Among 55 DILI patients, 10 cases presented with the hepatocellular pattern, 4 cases belonged to the mixed pattern, and 41 presented with the cholestatic pattern. Most cases reached the severity of grade 1 and 2. The rate of recovery in hepatocellular pattern, mixed pattern, and cholestatic pattern was 70.0%, 50.0%, and 41.5%, respectively. The proportion of the DILI cases treated with high dose (100mg) and prolonged duration (> 14 days) was significantly higher than standard dose and routine duration (100.0% vs. 18.1%, P < 0.05). Logistic regression analysis showed that high maintenance dose (OR = 1.028, P = 0.002), prolonged duration (OR = 1.208, P = 0.000), and number of hepatotoxic drugs (OR = 2.232, P = 0.000) were independent factors of tigecycline-associated DILI. Conclusion: Tigecycline was associated with liver injury, with a slightly higher incidence (5.7%) than the frequency of “frequent” (5%) defined by the Medical Dictionary for Regulatory Activities. Patients with a high maintenance dose and prolonged tigecycline regimen, as well as concomitant use of multiple hepatotoxic drugs should be paid more attention.